Better understanding determinants of dietary guideline adherence among Dutch adults with varying socio-economic backgrounds through a mixed-methods exploration - Josine M Stuber; Jeroen Lakerveld; Joline WJ Beulens; Joreintje D Mackenbach (Cambridge University Press, 2023)
Abstract Objective: Low dietary guideline adherence is persistent, but there is limited understanding of how individuals with varying socio-economic backgrounds reach a certain dietary intake. We investigated how quantitative and qualitative data on dietary guidelines adherence correspond and complement each other, to what extent determinants of guideline adherence in quantitative data reflect findings on determinants derived from qualitative data and which of these determinants emerged as interdependent in the qualitative data. Design: This mixed-methods study used quantitative questionnaire data (n 1492) and qualitative data collected via semi-structured telephone interviews (n 24). Quantitative data on determinants and their association with total guideline adherence (scored 0-150) were assessed through linear regression. Directed content analysis was used for qualitative data. Setting: Dutch urban areas. Participants: Adults aged 18-65 years. Results: A range of determinants emerged from both data sources, for example higher levels of cognitive restraint (β 5·6, 95 % CI 4·2, 7·1), habit strength of vegetables (β 4·0, 95 % CI 3·3, 4·7) and cooking skills (β 4·7, 95 % CI 3·5, 5·9), were associated with higher adherence. Qualitative data additionally suggested the influence of food prices, strong dietary habits and the social aspect of eating, and for the determinants cognitive restraint, habit strength related to vegetables, food prices and home cooking, some variation between interviewees with varying socio-economic backgrounds emerged in how these determinants affected guideline adherence. Conclusions: This mixed-methods exploration provides a richer understanding of why adults with varying socio-economic backgrounds do or do not adhere to dietary guidelines. Results can guide future interventions promoting healthy diets across populations.